Edukasi pemanfaatan cangkang telur ayam menjadi produk pangan di Desa Lampisang Kabupaten Aceh Besar - MS, Andriani; Miko, Ampera; Hadi, Abdul; Khazanah, Wiqayatun (Politeknik Kesehatan Kemenkes Aceh, 2024)
Environmental waste that will be utilized as a product that has a high enough selling value and is friendly to the environment is eggshell processing. Indonesia is one of the many egg consumers from year to year with a variety of processed food products. The number of eggs eaten both chicken eggs and duck eggs makes the eggshell waste quite a lot. Therefore, this eggshell waste can be processed into one of the products, namely Cookies which is a food snack product, as a decoration or handicraft, as a producer of organic fertilizer, and so on. In general, this community service activity aims to increase community knowledge in order to process various foods using chicken eggshells. From the results of the acquisition of the average value of knowledge and skills of participants who took the pre-test and post-test, it can be seen that there was an increase in participants' knowledge by 41.20. From these results, it can be said that statistically there is a significant increase (p-value <0.05) between knowledge before and after education with a p value = 0.000. Education on the utilization of eggshells into processed products has a positive impact on increasing knowledge of the utilization of eggshells into processed food products.